Seasonal Evolution of Canopy Stomatal Conductance for a Prairie and Maize Field in the Midwestern United States from Continuous Carbonyl Sulfide Fluxes. Issue 6 (13th March 2020) - Berkelhammer, M.; Alsip, B.; Matamala, R.; Cook, D.; Whelan, M. E.; Joo, E.; Bernacchi, C.; Miller, J.; Meyers, T.
Abstract: There are inherent challenges in scaling stomatal conductance (g s ) from leaf to canopy particularly over seasonal time scales when species distribution and canopy structure evolve. We address this gap using carbonyl sulfide (OCS) and CO 2 fluxes from a predominantly C3 prairie and C4 maize field in the midwestern United States. The g s derived from OCS fluxes captured a transition in the stomatal limitation on gross primary productivity (GPP) through the growing season as well as seasonally persistent g s dynamics such as temperature optimum and a positive response of nighttime g s to vapor pressure deficit. Near the termination of the prairie growing season, we observed a decrease in the relative OCS to CO 2 flux that we hypothesize emerged from a rising contribution of C4 plants to productivity. The results show how plot‐scale OCS and CO 2 fluxes can be used as a trace gas diagnostic for transitions in the limiting factors for community GPP. Key Points: Canopy stomatal conductance was derived from carbonyl sulfide (OCS) fluxes at maize and prairie sites in the midwestern United States Seasonal changes in the ratio of canopy stomatal conductance to GPP elucidated phenological transitions in community photosynthesis Daytime and nighttime OCS and CO 2 fluxes can be used for diagnostic trace gas signatures associated with C3 and C4 productivity